The Sufi trend in Adeeb Kamal El-Din's poetry - Muntaha Rahima Issa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Sufi poetry is one of the arts that emerged in the Islamic era and has developed and benefited from the Arab heritage, and that the language of Sufi poetry is characterized by its beauty and diversity of methods. And asceticism in this world, and after the researcher was briefed on the poetic collections of Arab poets in the modern era, she found that the poet Adeeb Kamal al-Din took in some of his poetry the Sufi approach as his method. It is the pure love of God Almighty. Accordingly, the title of the research was characterized as ((The Sufi Attitude in the Poetry of Adeeb Kamal Al-Din)).